Individual, organizational and environmental factors affecting work-life balance - Mokana, Muthu Kumarasamy (2016)
Finding a balance between work life and personal life has become a worldwide trend. Understanding factor that could affect work-life balance is important in rectifying this problem. Based on Conservation of Resources (COR) Theory, this study aims to examine direct relationship between emotional intelligence, spiritual intelligence, job engagement, work overload, technology advancement, and work-life balance. It also investigates moderating effect of organizational support on the relationship between emotional intelligence, spiritual intelligence, job engagement, work overload, technology advancement, and work-life balance. A total of 1,899 questionnaires were personally distributed to police officers at police headquarters in Peninsular Malaysia. Of 1,899 sets distributed, only 1,566 sets were returned and usable for further analysis, representing a response rate of 85%. Partial least squares (PLS) was used to evaluate the measurement model and structural model. The results support the hypotheses that emotional intelligence and job engagement are positively related to work-life balance. On the contrary, work overload and technology advancement are found to be negatively related to work-life balance. Additionally, spiritual intelligence is not found to be significantly and positively related to work-life balance. Finally, organizational support only moderates the relationship between job engagement and work-life balance. Theoretical and practical implications of the findings, as well as limitations and directions for future research, are discussed. The findings of this study provide evidence on the applicability of conservation of resources (COR) theory in explaining the factors affect work-life balance. Based on these findings, organizations must focus the variables of emotional intelligence, job engagement, technology advancement and work overload